Beethoven : the music and the life - Lockwood, Lewis (New York : W.W. Norton, 2003)
In this portrayal of the world's most famous composer, Lewis Lockwood interweaves his subject's musical and biographical dimensions and places them in their historical and artistic contexts. Written for the lay reader, the book describes the special problems Beethoven faced as a highly gifted artist who fulfilled his destiny as Mozart's main successor while remaining a true, rebellious original. It sketches the turbulent personal, historical, political, and cultural frameworks in which Beethoven worked and demonstrates their effects on his music. Finally, it turns to the composer in his last years, with great achievements behind him, surmounting the crisis of finding still further artistic paths by which to continue. Also, by providing glimpses into the composer's sketchbooks and autograph manuscripts, Lockwood allows us to gain substantial insights into Beethoven's compositional methods.
Includes bibliographical references (p. [559]-578) and indexes.
Keywords: Beethoven, Ludwig van, -- 1770-1827.; Beethoven, Ludwig van, -- 1770-1827 -- Criticism and interpretation; Composers -- Austria -- Biography